Pendampingan Nagham Qur’an sebagai Upaya Peningkatan Kualitas Bacaan Al-Qur’an Masyarakat Desa Marga Mulya, Kabupaten Tangerang: Strengthening Qur’anic Nagham in Community Religious Empowerment in Marga Mulya Village, Tangerang Regency - Adam Kholik; Wajihi Firda; Muhammad Dini Rahmatilah; Ahmad Jamil (Khadimul Mujtama’: Journal of Community Service, 2025)
This community service activity was conducted in Marga Mulya Village with a focus on assisting nagham Qur’an learning as an effort to improve the quality of Qur’anic recitation and spiritual appreciation within the community. The program was motivated by the limited ability of community members to recite the Qur’an with well-structured melodies, despite their basic reading competence. In addition, low self-confidence and the lack of systematic guidance have become challenges in strengthening the art of Qur’anic recitation at the community level. This community service aimed to enhance the quality of Qur’anic recitation through the reinforcement of tajwid and nagham Qur’an, while fostering awareness that the beauty of recitation is an integral part of worship. A participatory approach was employed, involving initial observation, gradual recitation assistance, and collective reflection with community members. The results indicate improvements in participants’ ability to recite the Qur’an with more organized melodies, increased self-confidence in recitation, and the development of a supportive and participatory learning environment. Furthermore, the activity strengthened social interaction and opened opportunities for the sustainable continuation of nagham Qur’an learning within the community. Overall, this community service demonstrates that contextual and empathetic nagham Qur’an assistance is effective in strengthening the religious quality of community life.